Analysis of Pre-Service Teacher Abilities in Professional Training Program on Aspects of Personality, Learning, Micro-Teaching, and Lesson Plan Development - Sutirna, Sutirna; Intisari, Intisari (Universitas Tanjungpura, 2023)
The aim of this study was to assess students' ability to engage in PLP (Professional Training Program) within schools. The research methodology employed a descriptive qualitative approach, utilizing surveys and direct observation of students participating in PLP activities. The assessment instrument included standards related to personality, learning, lesson plan development, and micro-teaching. The study involved PLP participants at the selected school sites. The results of the assessment, conducted by the supervising teacher and PLP assistant lecturer, revealed that PLP participants excelled in the aspects of personality, learning, lesson plan development, and micro-teaching.Keywords: PLP, Personality, Learning, Lesson Plan Development, Micro Teaching